Exploring the characteristics of newly defined at-risk drinkers following the change to the UK low risk drinking guidelines: a retrospective analysis using Health Survey for England data - Philippa Case; Linda Ng Fat; Nicola Shelton (BMC, 2019)
Abstract Background Alcohol guidelines enable individuals to make informed choices about drinking and assist healthcare practitioners to identify and treat at-risk drinkers. The UK Low Risk Drinking Guidelines were revised in 2016 and the weekly guideline for men was reduced from 21 to 14 units per week. This study sought to retrospectively establish 1) the number of additional at-risk male drinkers in England, 2) which demographic characteristics were associated with being an at-risk drinker under the previous versus new guidelines. Methods Average weekly alcohol consumption for men aged 16+ from the cross-sectional nationally representative Health Survey for England were used to 1) calculate annual population prevalence estimates for newly defined at-risk (> 14 to ≤21 units/week) male drinkers from 2011 to 2015 (N = 3487-3790), and 2) conduct logistic regression analyses for at-risk vs low risk male drinkers under the previous (> 21 vs ≤21 units/week) and new (> 14 vs ≤14 units/week) guidelines to assess characteristics associated with being at-risk drinkers under each guideline using 2015 data (N = 2982). Results Population prevalence estimates of newly defined at-risk drinkers ranged from 10.2% (2014 = 2,182,401 men)-11.2% (2011 = 2,322,896 men). Under the new guidelines, men aged 55-74 (OR = 1.63,95% CI = 1.25-2.12); men in managerial/professional occupations (OR = 1.64,95% CI = 1.34-2.00); current smokers (OR = 2.26,95% CI = 1.73-2.94), ex-regular smokers (OR = 2.01,95% CI = 1.63-2.47) and ex-occasional smokers (OR = 1.85,95% CI = 1.25-2.74); men from the North East (OR = 2.08,95% CI = 1.38-3.13) and North West (OR = 1.91,95% CI = 1.41-2.60) of England all had greater odds, and non-white men had reduced odds (OR = 0.53,95% CI = 0.34-0.80) of being at-risk drinkers, as they had under the previous guidelines. Under the new guidelines only: a higher percentage of at-risk drinkers aged 16-34 (32% vs 19%) attenuated the odds of men aged 35-54 being at-risk (OR = 1.18,95% CI = 0.92-1.51); a higher percentage of married at-risk drinkers (37% vs 24%) attenuated the odds of single men being at-risk (OR = 1.28,95% CI = 0.99-1.67); men from the West Midlands (OR = 1.68,95% CI = 1.17-2.42) and London (OR = 1.53,95% CI = 1.03-2.28) had greater odds of being at-risk drinkers. Conclusions The change to the Low Risk Drinking Guidelines would have resulted in more than 2 million additional male at-risk drinkers in England. Most groups with greater odds of being at-risk drinkers under the new guidelines were those already known to be drinking the most, strengthening the case for targeted screening and education. Additionally, under the new guidelines, a marked proportion of 16-35 year olds and married men were at-risk and men in the West Midlands and London had greater odds of being at-risk drinkers. These groups may benefit from specific education around the new Low Risk Drinking Guidelines.